2003
DOI: 10.5144/0256-4947.2003.10
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Histochemical Alterations in the Kidney Induced by Lead

Abstract: Background: Although lead intoxication is one of the most common forms of metal intoxication, the histochemical alterations in the renal tissues due to chronic lead exposure is limited and has not yet been well identified. Subjects and Methods: A total of 60 male Wistar albino rats (Rattus norvegicus) were exposed to lead acetate trihydrate (0.0, 0. 25, 0.5, 1.0 and 2% for 1 to 12 months) in drinking water to investigate the histological and histochemical alterations in the renal tissues due to lead. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Many animal studies have shown that lead is capable of causing oxidative stress in the kidney, liver, and brain (Ercal et al, 1996;Patra et al, 2001). The absorbed Pb is conjugated in the liver and passed to the kidney, where a small quantity is excreted in urine and the rest accumulates in various body organs, affecting and affects many biological activities at the molecular, cellular and intercellular levels, which may result in morphological alterations that can remain even after Pb levels have fallen (Jarrar, 2003;Sidhu & Nehru, 2004;Taib et al, 2004;Flora et al, 2006). The kidney is a sensitive target organ for lead exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Many animal studies have shown that lead is capable of causing oxidative stress in the kidney, liver, and brain (Ercal et al, 1996;Patra et al, 2001). The absorbed Pb is conjugated in the liver and passed to the kidney, where a small quantity is excreted in urine and the rest accumulates in various body organs, affecting and affects many biological activities at the molecular, cellular and intercellular levels, which may result in morphological alterations that can remain even after Pb levels have fallen (Jarrar, 2003;Sidhu & Nehru, 2004;Taib et al, 2004;Flora et al, 2006). The kidney is a sensitive target organ for lead exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a relative high lead concentration might reach the cortex via blood flow than that would enter the medulla [10].…”
Section: Discussionmentioning
confidence: 99%
“…As known, kidney is the major excretory and also the final organ of clearance for most of the xenobiotics. Furthermore, kidney is the most vulnerable organ to lead toxicity (Jarrar, 2003). It is known that mercury can cause unplanned and occupational exposures and poisoning will created from inhalation, ingestion, and absorption through the skin (Ercal et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antioxidants, plant extracts and chelating agents have the potential to inhibit these effects (Kumar et al, 2013;Jarrar, 2003;Mehana et al, 2012;Ekor et al, 2010). Our findings showed that both NAC and DMSA ameliorated the decrease in serum and mRNA expression of antioxidants.…”
Section: Discussionmentioning
confidence: 99%